Nikoloz Baratashvili: The Blue Sky; Meditations By the River Mtkvari; Merani. - Donald Rayfield,; Venera Urushadze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
Nikoloz Baratashvili (1817-1845) is the greatest representative of Georgian Romanticism. His poetry has not been fully translated into English. In this issue of the journal, three of Baratashvili’s best known poems are published: Sky Blue (translated by Donald Rayfield: The Literature of Georgia. A History. Carzon). Meditations by the river Mtkvari and Merani (translated by Venera Urushadze.Anthology of Georgian Poetry, Tbilisi 1958). The Georgian text is published as cited in the edition by Pavle Ingorokva (Nikoloz Baratashvili. Works, 1959). The Editor